Impact of culture on refugee women's conceptualization and experience of postpartum depression in high-income countries of resettlement: A scoping review. - Saarah Haque; Mary Malebranche (PLoS ONE)
Background The global refugee population has reached a staggering 25.9 million. Approximately 16% of global refugees resettle in high-income countries which are often culturally very different from their home countries. This can create cross-cultural challenges when accessing health services, leading to inappropriate assessments, diagnoses and treatments if cultural background is not factored in. The impact of culture on the conceptualization and experience of postpartum depression (PPD) amongst migrant women has received growing attention in recent years, however, a specific focus on refugee and asylum-seeking women is lacking. Given the unique mental health challenges refugee women face, it is hypothesized that the interplay between culture and postpartum depression amongst refugee women may differ from other migrant women. Therefore, a scoping review was conducted to characterize what is known about the impact of culture on the conceptualization and experience of PPD in refugee women resettled in high-income countries. Methods and findings This study was conducted as a scoping review in accordance with the Joanna Briggs Institute's Methodology for Scoping Reviews. A systematic search of studies addressing the relationship between culture and postpartum depression amongst refugee women (including asylum-seeking women) resettled in high-income countries was conducted across 6 databases including MEDLINE, PsycINFO and SOCINDEX between June 2018 and August 2019. A total of 637 articles were found. Studies were eligible if they focused on refugee women who had a pregnancy during forced migration or upon resettlement in a high-income country and focused on the impact of culture on women's conceptualization and/or experience of PPD. Eight studies met inclusion criteria and were included in the final analysis, the majority of which were qualitatively driven. Four key themes emerged: 1) there are diverse conceptualizations and experiences of postpartum depression amongst refugee women; 2) mental health stigma has a significant impact on women's conceptualizations and experiences of postpartum depression and help-seeking behaviors; 3) cultural traditions and social support play protective roles in postpartum mental wellbeing; and, 4) host culture has a significant influence on the pregnancy and postpartum experience of refugee women. The overall themes align with those seen in the literature on migrant women in general, however significant research gaps remain. Conclusion The studies identified through this scoping review provide a rich description of the significant impact culture has on the conceptualization and experience of postpartum depression among refugee women resettled in high-income countries. Though overall themes align with those seen in the literature on migrant women in general, further research is needed to better characterize how culture impacts refugee women's experiences of PPD as a distinct sub-group of migrant women.